ANALISIS IMPLEMENTASI PENDEKATAN STEM DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR: STUDI KONTEKSTUAL DI KOTA SAMARINDA - Supriyatna, Yana; Suhartini, Erna; Raudhiah Zahra, Ince; Mannan, Muhammad Nur; Khaerani, Rosita Putri Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
STEM (Science, Technology, Engineering, and Mathematics) holds strong potential to promote 21st-century skills in elementary education, yet its implementation faces ongoing challenges. This study examines teachers’ understanding, instructional strategies, obstacles, institutional support, and the impact of STEM-based science learning in Samarinda, Indonesia. Using a descriptive qualitative-quantitative approach, data were collected from 18 teachers through questionnaires, interviews, reflections, and document analysis. Findings show that while teachers demonstrate basic understanding of STEM, especially in science and technology (mean score: 3.90), the integration of engineering and mathematics remains limited (3.60). Key barriers include limited training, insufficient time, and inadequate resources (3.23), with school support remaining general (3.00). Despite this, teachers actively seek resources and engage in informal collaboration. STEM practices reportedly increase student engagement, creativity, and critical thinking (4.10). The study highlights the need for practical training, contextual learning tools, teacher collaboration, and sustained policy support to strengthen STEM education at the elementary level.